Defining the perception of energy security: An overview - Indre Siksnelyte-Butkiene (Economies, 2023)
Energy security is recognized as a key element for the successful functioning of an entire energy system. However, the perception of energy security is contextual and there is no universally accepted definition of the concept. The current global concerns about climate change, human welfare and energy market challenges due to the COVID-19 pandemic, military conflicts, various geopolitical issues and scarcity of energy resources have affected the perception of the energy security concept as well. The research aims to define how energy security is perceived amid current global concerns and to identify the essential components. The four-tiered research methodology was developed and applied to determine the current perception of energy security. While the systematic literature review was conducted according to the SALSA (Search, Appraisal, Synthesis and Analysis) framework, it was found that the current perception of energy security consists of seven main components, these are: Availability, Affordability, Environmental Impact, Social Impact, Geopolitical Relationships, Government Effectiveness and Technological Development. The paper contributes to discourse development and clarification of perception of energy security and will be useful for further research, both dealing with the concept of energy security itself and developing composite indicators for energy security assessment.
Keywords: 330; energy security; energy policy; climate change; geopolitical relations; literature review